Αντισεισμικός σχεδιασμός κατασκευών και ανάλυση κόστους κύκλου ζωής για αντισεισμική ενίσχυση υφιστάμενων κτιρίων - Χαραλάμπους, Γιώργος (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This case-study aims to apply the procedure of ‘Life Cycle Cost Analysis’ as a decision tool for Limassol Municipality and provide optimum retrofitting strategies for two building categories. Seismic hazard and seismic vulnerability are the main factors that affect the life cycle cost but their quantification is a difficult task with many epistemic or aleatoric uncertainties. The application of this procedure consists of both economic and technical data. The probabilistic approach and the parametric study adds to the reliability of the present study. In the first chapter an introduction regarding the catastrophical consequences of earthquakes and the lack of seismic design in most structures is presented. In the second chapter the literature review needed for the application of the aforementioned procedure is reviewed. In the third chapter the methodology for applying the procedure is analyzed. In the fourth chapter the results of the application are presented along with a parametric study. In the fifth chapter the conclusions of the case study are presented. In the appendix the code used for applying the procedure is exported from Matlab.
Keywords: Life cycle cost analysis; Limassol municipality; Optimum retrofitting strategies; Seismic hazard; Seismic vulnerability; Earthquake; Lack of seismic design; Matlab; Ανάλυση κόστους κύκλου ζωής (ΑΚΚΖ); Δήμος Λεμεσού; Σταθμός προσεισμικής ενίσχυσης; Σεισμική επικινδυνότητα; Σεισμός; Αντισεισμική πρόνοια